Assessment of Local Tissue Responses to Subcutaneous Implantation of Polyetheretherketone and Polymethyl Methacrylate-Based Materials - Demyashkin, Grigory; Durasov, Mikhail; Muraev, Alexander; Silakov, Kirill; Milyukova, Darya; Ivanov, Sergey; Dzhenzhera, Georgy; Ushakov, Andrey (Scripta Medica, 2025)
Background/Aim. Assessment of local irritant effects following subcutaneous implantation of polyetheretherketone (PEEK) and polymethyl methacrylate (PMMA)-based devices, with determination of their biocompatibility and safety for intended applications in dental practice. Methods. The study used 30 male Wistar rats (200 g ± 10 g, 9–10 weeks old) to evaluate inflammatory responses to four subcutaneous implants (PEEK, 3DF, Apium, Bonlecule) over 7, 30 and 60 days. Histological analysis assessed cell infiltration, necrosis, neovascularisation, fibrosis and capsule formation using standardised scoring systems. Statistical comparisons were made via one-way ANOVA (p < 0.05) to analyse intergroup differences in tissue reactions. Results. Macroscopic examination showed stable implant integration with no structural changes, while microscopic analysis revealed mild mononuclear infiltration and progressive fibrous tissue replacement, with the strongest response in the Bonlecule group at day 7 and the weakest in PEEK by day 60. Histopathology indicated vascular dilation, reduced fibroblasts and increased immune cells, but no necrosis or fatty infiltration, with PEEK exhibiting the thinnest proliferation zone by day 60. Morphometric data confirmed Bonlecule had the thickest proliferation zone (91.9 µm at day 7), while PEEK showed the most significant reduction (28.34 µm by day 60). Conclusion. The study confirmed high biocompatibility of PEEK and PMMA implants, with PEEK showing optimal integration and minimal tissue reaction, making it suitable for dental applications. The 3DF implant demonstrated the lowest bioresorption, remaining structurally intact over the two-month observation period. These findings support the clinical use of these materials, particularly PEEK, which meets all biocompatibility requirements with moderate immune response and vascularisation.